The Phenomenon of Synonymy in Uzbek and Chinese Languages - Qodirova Madina Xoliyorovna (Zien Journals, 2024)
Synonymy, the existence of multiple words or phrases with similar meanings, is a linguistic phenomenon of great significance and complexity. This article delves into the phenomenon of synonymy in two distinct languages, Uzbek and Chinese, shedding light on the diverse manifestations, cultural influences, and linguistic intricacies that shape synonym usage in each language. Through a comparative analysis, it explores the similarities and differences in how synonymy operates in these languages, offering valuable insights into the interplay between language, culture, and linguistic diversity
Keywords: Synonymy; Linguistic phenomenon; Uzbek language; Chinese language